إطار تصوري لقیاس الأداء في المؤسسات الصغیرة والمتوسط - دراسة حالة مؤسسة Aca Achourبالمسیلة - - قروش, عيسى; برحومة, عبد الحميد (جامعة الوادي - University of Eloued, 2015)
This study aims in the theoretical part, to illustrate the importance of performance measurement in small and medium enterprises, as one of the main solutions to the managers to know the opportunities and threats faced the enterprise in the current environment, which is highly competitive and rapidly changed. The study showed in one hand the inadequacy of applying the general performance measuring systems in SMEs environment, and on the other hand, it showed the lack of models designed specifically SMEs, that are adapted with the financial, organizational, and human specifications in these enterprises. In the practical side, we have tried to build a conceptual framework to measure the performance in the entreprise under study using the integrated performance model (Laitenen, 2002) and through dropping the performance indicators currently used and those that have the ability to use in the future.
Conceptual framework for measuring performance in the SME A case study on Aca Achour Enterprise in M’sila
مقال
Keywords: Small and medium enterprises, models of measuring performance, integrated performance model.